Modification of formaldehyde method, optimisation of formaldehyde content in Rastrelliger faughni and Euthynnus affinis and storage studies / Abdul Ghani Abu Samah - Abu Samah, Abdul Ghani (2008)
The purposes of this study were to modify method for formaldehyde determination content in fish, to determine optimum natural formaldehyde content in mackerel (Rastrelliger faughni) and kawakawa (Euthynnus affinis) and also to study their acceptability during storage. The modification of the formaldehyde analysis method was done for mackerel based on AOAC 931.08 and Nash’s methods. Detection limit of formaldehyde using modified formaldehyde method was 0.025 ppm with condition variables: 50 gram sample, pH of sample 2.2-2.4 and volume distillated 250 milliliter. Recoveries were obtained 84.8% and 63% when 0.5 ppm and 3 ppm spikes of formaldehyde were applied respectively. The advantages of the modified formaldehyde method are: several hazardous chemicals were no longer used, interferences could be avoided and time of analysis could be shortened. There were no significant difference in formaldehyde absorbance at the 5% level for the case of formaldehyde working standards 0.1 to 0.9 ppm which were kept in chilled temperature (5oC) for less than 10 days followed by mixing with freshly prepared Nash’s reagent or mixing with Nash’s reagent which were kept in chilled temperature (5oC) for not more than 24 hours before being put in cuvettes and then promptly kept in closed box for not more than 3 hours before detecting their absorbances using UV spectrophotometer.